2018
DOI: 10.29173/cjfy29347
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Association between Parent and Child Sport Participation in Canada: A General Social Survey Study

Abstract: Research has shown a relationship between parent sport participation and child sport participation. With a sample of 1,064 respondents from the 2010 General Social Survey, this study examined how child sport participation is associated with parent sport participation, household income, parent education level, and parent sex. Results found that respondents with a child aged 5-12 who participated in sport over the past 12 months were more likely to have done so themselves too. (OR = 4.39, 95% CI = 2.44-7.89, p &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Despite the many benefits of sports participation for children, studies in multiple countries have shown that sports participation is lower among children from low-income families than among children from middle- or high-income families (e.g., [ 4 , 5 , 6 , 7 ]). Parents play an important role in facilitating their children’s sports participation [ 3 ], but few studies to date have focused on understanding parent-related factors influencing children’s sports participation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the many benefits of sports participation for children, studies in multiple countries have shown that sports participation is lower among children from low-income families than among children from middle- or high-income families (e.g., [ 4 , 5 , 6 , 7 ]). Parents play an important role in facilitating their children’s sports participation [ 3 ], but few studies to date have focused on understanding parent-related factors influencing children’s sports participation.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the many benefits of sports participation for children, studies in multiple countries have shown that sports participation is lower among children from low-income families compared to children from middle- or high-income families (e.g., [ 4 , 5 , 6 , 7 ]). This inequality is also observed in The Netherlands.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies in several countries have shown that sports participation is lower among children from low-income families compared to those from middle-or high-income families (e.g., Refs. [4][5][6]). As such, sports clubs seem to be less accessible to children, who may benefit most from sports participation.…”
Section: Introductionmentioning
confidence: 99%